Julia's house goes home - Hatke, Ben (First Second, 2021)
"Julia's flying house has come down to earth--and sprouted legs! Now it roams the landscape looking for the perfect spot to settle down. But just as Julia spots the Perfect Spot, off in the distance--her walking house trips! It tumbles down a steep mountain side, and Julia and her creatures are scattered across the hills while her runaway home continues rolling off on an adventure of its own"--Provided by publisher.